Continuous feral horse grazing and grazing exclusion in mountain pampean grasslands in Argentina - de Villalobos, Ana Elena (2010)
This paper evaluates changes in the composition and structure of plant communities and plant functional groups associated with the continuous presence of feral horses in mountain pampean grasslands in Argentina in order to explore the potential effects of horse removal on vegetation restoration. Specific and functional richness, diversity, evenness, spatial heterogeneity and above-ground biomass were compared between areas subjected to ten years of intensive grazing by horses and exclosures of the same age. Forbs, shrubs and rosettes were more abundant after ten years of grazing, while the spatial heterogeneity of perennial grasses was higher in long-term grazed areas. Nevertheless, grasslands showed good recovery after horse removal, with greater species diversity and evenness, higher abundance of perennial grasses, greater above-ground biomass and lower percentages of exotic species. An understanding of the effect of feral animals on plant communities will lead to the design of a strategy of adaptive management and monitoring tools for measuring the condition of grasslands.